Using Problem-Based Learning to Improve 12th Grade Students’ Learning Outcome of Mathematical Three-Dimension - Suprihatin, Titin (International Journal Labs, 2022)
Mathematics learning about three dimensions has difficulties in solving learning, for that it requires a fixed learning method, one of which is problem-based learning. This study aims to understand and solve mathematics learning problems about the third dimension with the problem-based learning method. The samples taken were class XII IPA 4 in the 2019/2020 academic year as many as 25 students. The instrument used is a written test with 5 assessments. It is a Classroom Action Research (CAR) on mathematics learning problems about three dimensions in class XII IPA-4 Semester 1 of the 2019/2020 academic year at SMA N (Public Senior High School) 9 Cirebon City. The data collection techniques conducted were observation, interviews, data processing, and documentation. The results of the research from the initial study data obtained that from the number of students 25 students only 9 students who have a complete score and the rest, namely 16 students do not get a complete score, with a total student score of only 1702 and an average of 68.08 and gets a percentage of completeness 36%. Then improvements were made in two cycles, in the first cycle with two assessments, in the first cycle it produced an average score of 74.92 and the percentage of completeness was 56%. While in Cycle II, the average score was 78.64 and the percentage of completeness was 80.77%, thus the percentage of completeness from Pre Cycle I, Cycle I, and Cycle II increased.